Analisis Risiko dengan Menggunakan Metode Domino pada Rehabilitasi dan Renovasi Perpustakaan dan Laboratorium IAIN Ambon - Febri Linda Keliola; Nelda Maelissa; Maslan Abdin (Jurusan Teknik Sipil, 2022)
Construction work can cause Work Accident Risk, therefore the implementation of construction work is required to implement an occupational safety and health (K3) management system at the work site. However, the IAIN Ambon Library and Laboratory Rehabilitation and Renovation project was not implemented. So this study aims to obtain the Dominant Occupational Accident Risk, the causal factors and how to respond to these causal factors. The method used in this study is a semi-quantitative analysis method combined with the domino method. Semi Quantitative Analysis in the form of distributing questionnaires containing a scale of 'likelihood' and 'consequency' values and processed with SPSS, then analyzed with a Risk Matrix while the domino method is used to identify factors causing work accidents. The results obtained: 1. There are 8 Dominant risks (1) Workers are exposed to noise from iron cutting machines, (2) Workers' heads are exposed to wood impact during baking installation, (3) Workers' eyes are exposed to Splashing of Concrete Mixture, (4) Workers' breathing is disturbed due to ceramic cutting dust, (5) Workers are exposed to noise from ceramic cutting tools, (6) Workers' eyes are exposed to splashes from liquid paint, (7) Workers' breathing is disturbed due to ACP cutting dust, (8) Workers are exposed to noise from ACP cutting tools. 2. Factors causing work accidents (1)Lock of control/Management (2) Basic Cause of accident (3) Immediate cause/symptoms (4) Incident (5)Loss. 3.Response to factors causing work accidents, namely (1) Risk Reduction (2) Risk Transfer.